The effectiveness of cognitive and psychomotor domain of culinary art students’ performance after internship in private colleges - Harun, Hairuddin; Abdul Rahman, Abdul Wafi; A. S., Noorazman; Mohd Noor, S.N.F.; Md Sahak, Adibah Aishah (EDP Sciences, 2018)
With the demand of culinary arts graduates in hospitality industry, more higher learning institutions especially private colleges offer the programs. The course syllabus of culinary arts is specifically designed to provide a strong foundation for students who aspire to be chefs in the local and international fields. Students are equipped with a basic education in the culinary skills and knowledge associated with the cognitive and psychomotor domain. This study investigates the influence of the cognitive and psychomotor domain effect to private college student’s performance after internship. The internship program is gradually enhancing the students’ knowledge; confidence level and psychomotor performance which enable them to at least gain confidence when performing their practical assessment after coming back from internship. This is a positive indication in the beginning of the students’ life before expose into a real life work situation. Thus, this research can be a guidance for the private institutional lecturers to look into the effectiveness of cognitive and psychomotor domain of culinary art students’ performance in their internship programs.